Pelatihan Pembuatan Pori Busa (Pupuk Organik desa Bug-Bug Kecamatan Lingsar) - Taufik Rahman; M. Audi Adyan; Fathurrahman Fathurrahman; Baiq Annisa Sulistia Ayuni; Srikandi Ayu Kartini; Nur Hafizatun Aulya; Aulia Padhila Ersu; Yuni Nur’Azizah; Maswinda Maswinda; Baiq Himayatussifa Salmiah; Ida Ayu Oka Suwati Sideman (Pascasarjana Universitas Mataram, 2023)
Bug-Bug Village, which is located in Lingsar District, West Lombok Regency, has the potential for regional development as an agricultural area, because apart from the agricultural area being 42% of the total village area, it is also recorded that 27.45% of the population works as farmers. As a farmer, the need for subsidized fertilizer is certainly very large. Unfortunately, the government's ability to provide subsidized fertilizer is only 37-42%. By studying these conditions, the ability of farmers to make their own organic fertilizer is really needed. The benefits of organic fertilizer on the health of production results, the health of the surrounding environment and also the health and welfare of farmers, is also the reason that supports the